Sosialisasi Peran Masyarakat dalam Mitigasi Dampak Abrasi terhadap Kerusakan Infrastruktur Jalan dan Lingkungan di Pesisir Pantai Jerowaru - Karyawan, I Dewa Made Alit; Hasyim; I Dewa Gede Jaya Negara; Rohani; Humairo Saidah; I Wayan Yasa (Universitas Mataram, 2024)
Jerowaru Beach, located on the southern coast of Lombok Island, is facing a significant threat due to coastal abrasion, which damages both road infrastructure and the environment. Abrasion, the process of land erosion caused by ocean waves, leads to the erosion of coastlines, damage to coastal protective structures, and alterations in coastal ecosystems. At Jerowaru Beach, the effects of abrasion include road damage and the loss of vital natural habitats such as mangrove forests, which are essential for coastal protection and supporting local species. Raising community awareness about the role they can play in mitigating abrasion's impact is a crucial first step toward reducing damage and enhancing environmental conservation efforts. On July 29, 2024, a socialization event was held at Bale Mangrove Jerowaru Beach, involving PMD KKN students and local residents. This event included training on mitigation techniques such as mangrove planting and the construction of coastal protection structures, as well as awareness campaigns through local media and community events. The socialization efforts resulted in increased public understanding of the impact of abrasion and the importance of mitigation measures. Active community participation in rehabilitation activities and collaboration with relevant stakeholders, including the government and NGOs, has also enhanced the effectiveness of these efforts. This socialization serves as a foundation for developing further mitigation strategies that involve ongoing community involvement and continuous monitoring. In conclusion, community engagement in mitigating abrasion at Jerowaru Beach is crucial for protecting road infrastructure and maintaining environmental sustainability. Recommendations include developing abrasion-resistant infrastructure, securing funding, and conducting regular monitoring to ensure the success of mitigation strategies